2017
DOI: 10.1111/efp.12348
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of Scots pine stilbene synthase and chalcone synthase genes to Heterobasidion annosum infection

Abstract: Summary Phenolic compounds are essential components of the defensive chemical arsenal of conifer trees. This chemically diverse group encompasses stilbenoids, flavonoids, isoflavonoids, proanthocyanidins and lignans. All of them are produced from the common precursors, CoA esters of the phenylpropanoids: p‐coumaroyl‐CoA, cinnamoyl‐CoA, caffeoyl‐CoA and feruloyl‐CoA. Two classes of enzymes, stilbene synthases and chalcone synthases, play important roles in the biosynthesis of plant phenolics, such as the conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In addition, an earlier finding revealed that the terpene concentration in Scots pine trees highly susceptible to H. annosum was significantly higher compared to less susceptible trees, while δ-3-carene concentration was negatively correlated with lesion length in trees . Stilbene synthase also plays a role in the induced responses of Scots pine to fungal infection of H. annosum (Kovalchuk et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, an earlier finding revealed that the terpene concentration in Scots pine trees highly susceptible to H. annosum was significantly higher compared to less susceptible trees, while δ-3-carene concentration was negatively correlated with lesion length in trees . Stilbene synthase also plays a role in the induced responses of Scots pine to fungal infection of H. annosum (Kovalchuk et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although molecular mechanisms of flavonoid biosynthesis have been extensively studied in many plants, few studies have been performed in Capsicum , an important vegetable. With the availability of published genomes, we have carried out comprehensive mining of the type III PKS genes in three Capsicum species [ 20 , 21 ]. This gene has been extensively studied, which has been revealed to catalyze the committed step of flavonoid biosynthesis in a wide variety of plants and other organisms [ 14 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like other type III PKSs, CHSs often exist as small-to-large families in flower plants, resulting from segmental or whole-genome duplication and nucleotide substitution [ 16 , 17 ]. They are constitutively expressed among tissues and across different developmental stages [ 18 ]; and they are induced by external factors such as drought, salinity, low temperature, UV, wounding and biotic infections [ 19 , 20 , 21 , 22 , 23 ,]. Plant CHSs play significant roles in physiological, pathological and developmental processes such as flower pigmentation, fruit development and biotic and abiotic resistance [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In any case, the timing of the infection is vague because the size of the genet is not only dependent on the age of colonization but also other factors, such as frequency of root contacts, the occurrence of competing and antagonistic microorganisms in the rhizosphere [27,30], soil properties [23,31,32], and improved resistance of the trees with aging [17,23,24]. Furthermore, differences in the inherent tolerance or susceptibility of Scots pine genotypes to Heterobasidion infections [33,34] may influence the spread rate of the disease. Moreover, the rate of the fungal spread could slow down due to reduced vitality of the Heterobasidion mycelium, for example, due to aging [8] and/or virus infections [35][36][37].…”
Section: Incidence Of Heterobasidion Root Rot In the Previous Scots Pine Rotationmentioning
confidence: 99%